Assessment of cardiac function and electrocardiographic findings in patients with Wilson's disease. (September 2019) - Karhan, Asuman N.; Aykan, Hayrettin H.; Gümüş, Ersin; Dönmez, Yasemin; Alehan, Dursun; Özkutlu, Süheyla; Demir, Hülya; Saltık Temizel, İnci N.; Özen, Hasan; Yüce, Aysel
Abstract: Background: This study evaluated cardiac function using tissue Doppler echocardiography and assessed electrocardiographic findings in children diagnosed with Wilson's disease. Method: Asymptomatic patients with a diagnosis of Wilson's disease (n = 43) were compared to healthy controls (n = 37) that were age and gender matched. Results: The standard electrocardiographic and conventional echocardiographic examinations were similar in both groups. The left ventricular ejection fraction, shortening fraction, and diastolic function were not significantly different between the two groups. The Tei index for mitral lateral, mitral septal, tricuspid lateral, tricuspid septal, and inter-ventricular septum on tissue Doppler echocardiography was higher in the patient group, yet it did not reach statistical significance. Mitral lateral and septal systolic annular velocity values were significantly lower in the patient group when compared to the control group (p = 0.02 and 0.04, respectively). Also, mitral lateral and septal isovolumetric contraction time values were higher in the patient group (p = 0.04). Although the left ventricular values were not significantly different, relative left ventricular wall thickness was higher in the patient group when compared to the control group, and concentric remodelling in the left ventricle was found in 7 (16%) of 42 patients. QT interval (p = 0.02) and P-wave dispersion values (p = 0.04) were significantly higher in the patient group compared to the control group, and these tend to predict arrhythmias. Conclusion: Our study based on the tissue Doppler echocardiography assessment indicated a subclinical systolic, rather than diastolic, dysfunction in the myocardium with increased QT interval and P-wave dispersion, despite the young age of the patients and short disease duration.